Antioxidant and antimicrobial effect of turmeric oil, boswellia oil and neem oil on pathogenic and food spoilage microorganisms - SHEETAL CHOUDHARY; MOHAMMAD HANEEF; NAVEEN SHARMA; AMIT SHARMA; GOLDIE GABA (International Journal of Pharma and Bio Sciences, 2019)
Oils extracted from the parts of plant possess a plethora of ethno botanical activity. They have been extensively utilized in perfume, food, pharmaceutical and cosmetic industry as fragrances, flavoring and therapeutic agents. This study investigates antioxidant and antimicrobial potential of herbal essential oils namely turmeric, neem and boswellia in order to extend their protective activity against infections and food spoilage. The microorganisms utilized in the research were a strain of gram positive bacteria; Staphylococcus aureus, gram negative bacteria: Escherichia coli and two strains of fungi: Candida albicans and Aspergillus brasiliensis. The essential oils were extracted in-house by adopting methods standardized for industrial purposes. The antioxidant potential of the obtained essential oils was analyzed by FRAP assay while antimicrobial effect was examined by the percentage of growth inhibition on test microorganisms. Viable strains were nurtured in culture media over a period of 21 days to observe the antimicrobial potential. The results from the present study revealed strong antioxidant potential of Turmeric oil followed by Boswellia oil and least effect was seen in case of neem oil. Similar pattern was observed in case of antifungal activity against Candida albicans (NCIM-3471, Pune); Turmeric oil >Boswellia oil >Neem oil while the pattern of antifungal activity differed from the former results. The pattern of inhibitory effect against Aspergillus brasiliensis(NCIM-1196, Pune) was not significantly different in case turmeric and boswellia oil although turmeric oil still had better activity followed by neem oil. The antibacterial effect against both the strains Staphylococcus aureus (NCIM-5345, Pune) and Escherichia coli (NCIM-2065, Pune) was observed to be Turmeric oil ≥ Boswellia oil >Neem oil. It was concluded that Turmeric oil and Boswellia oil exhibited marked antioxidant and antimicrobial activity.